Evaluasi User Experience Pada Social Application Mobile HAGO Menggunakan Metode Enhanced Cognitive Walkthrough - Tri Andre Mahadika Putra; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
HAGO is a miniature social game app made up of various fun and challenging types of games. Since its launch at the playstore on March 23, 2018, few months have become the number one on the "top free apps" playstore. This success is not far from the user experience provided by hago itself. But a system must have some problems or constraints found in particular the new release system. To find those issues needed to hold an evaluation especially in the usability section. The enhanced cognitive walkthrough is one of the usability evaluations based on the user experience. This method would give the scenario a series of tasks to be worked on and 10 questions about the assignment to the evaluation. Six expert examiners, 2 expert, and 2 novice. The evaluation of the hago application shows most troubling problems in hidden (h) type of hidden (h) problems in the main functions of the social application mobile hago. The average issues issues arise in the problem of seriousness and 3 and affect the major function of hago applications. Thus, hago's applications are quite easy for both experienced and new visitors. But new users take quite a while to understand this application